2014
DOI: 10.1186/1916-0216-43-15
|View full text |Cite
|
Sign up to set email alerts
|

Age related changes to the dynamics of contralateral DPOAE suppression in human subjects

Abstract: BackgroundThe two ears are linked with a neural pathway such that stimulation of one ear has a modulating effect on the contralateral cochlea. This is mediated by cochlear afferent neurons connecting with olivo-cochlear efferents. The monitoring of this pathway is easily achieved by measuring contralateral suppression of otoacoustic emissions, and there is some clinical value in the ability to assess the integrity of this pathway. An important step in an evaluation of clinical utility is to assess any age-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…3 in Ref. ( 98 )]; (2) OAE suppression decreases with increasing age in listeners with normal audiometry ( 117 , 118 ); and (3) OAE suppression appears to be larger for OAE measured in the left than in the right ears ( 119 ), although other studies have reported greater suppression in the right ear ( 120 ). These factors (CAS bandwidth, age, and test ear) can differ across studies, which can make across-studies comparisons of CAS-activated MOC effects difficult.…”
Section: Olivocochlear Efferent Effects In Humansmentioning
confidence: 91%
See 1 more Smart Citation
“…3 in Ref. ( 98 )]; (2) OAE suppression decreases with increasing age in listeners with normal audiometry ( 117 , 118 ); and (3) OAE suppression appears to be larger for OAE measured in the left than in the right ears ( 119 ), although other studies have reported greater suppression in the right ear ( 120 ). These factors (CAS bandwidth, age, and test ear) can differ across studies, which can make across-studies comparisons of CAS-activated MOC effects difficult.…”
Section: Olivocochlear Efferent Effects In Humansmentioning
confidence: 91%
“…Konomi et al ( 117 ) showed that the onset latency of DPOAE suppression by CAS increases with increasing age from about 60 ms for 2-year-old children to 150 ms for 50-year-old adults, without a change in the time constant of suppression. They argued that the increased latency might reflect deterioration in auditory brainstem function involved in the MOC reflex.…”
Section: Olivocochlear Efferent Effects In Humansmentioning
confidence: 99%
“…Because the MOC reflex is binaural, contralateral sound can activate MOC fibers to the ipsilateral ear and suppress responses such as otoacoustic emissions (Collet et al, 1990). Studies of "contra-sound suppression" suggest that MOC reflex strength declines with age (Kim et al, 2002;Jacobson et al, 2003;Konomi et al, 2014;Lisowska et al, 2014). Given the hypothesized role in the control of masking, this reflex decline may contribute to problems with hearing in noise in the aging ear.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous datasets consistent with maturation of higher order processes, such as auditory stream segregation (e.g., Oh et al , 2001). There are also data on suppression of distortion-product otoacoustic emissions, an indicator of efferent function, indicating that the medial olivo-cochlear reflex is strongest in neonates and declines with each decade of life, from childhood into old age (Konomi et al , 2014). A stronger MOC reflex would be expected to improve performance when a signal is delayed relative to masker onset, but it is unclear how it would contribute to poorer thresholds in the gated condition, as observed in the present data.…”
Section: Discussionmentioning
confidence: 99%